VD_FINDINFO Jug / 2012 / 252 vom 6. Juni 2012 - VD Tribunal cantonal (2012)
IN DUBIO PRO REO, CONSTATATION DES FAITS, INDEMNITÉEN GÉNÉRAL | 29 Cst., 10 CPP (CH), 398 al. 2 CPP (CH), 398 al. 3 let. a CPP (CH), 429 CPP (CH)